Biomechanical analysis of schwingen (swiss wrestling) to gain insights into head, neck and knee injury risks - Lorenzetti, S.; Oberhofer, K.; Löhrer, M.; Lüthy, F. (ISBS Proceedings Archive (Michigan), 2020)
This research project aims to reduce incidences of injuries to the head, neck and knee in schwingen (Swiss wrestling) by means of biomechanical analysis. In this pilot study, kinematic and kinetic data were acquired during key manoeuvres in schwingen for the first time. Two professional athletes at Swiss national level in schwingen were performing the so-called Kurz, the Hüfter and the bridge in a simulated competitive setting. The peak vertical ground reaction force, acting on the back as the opponent was hitting the ground during the Hüfter, was measured to be 11500 N; while the peak vertical ground reaction force on the head during the bridge was 2360N, respectively. The knee flexion angle of the leading leg during the Kurz was 55°, with the total knee joint forces being 410N in the anterior-posterior direction and 400N in the medio-lateral direction, respectively. In comparison with reported cervical spine injury risks in American football and sumo wrestling, injury mechanisms at the level of the head, neck and knee in schwingen are likely a result of the applied forces from dynamic throws, in combination with extreme joint ranges of motion during fixed grips and defensive manoeuvres such as the bridge. An extended biomechanical analysis of the applied forces, moments and joint kinematics during schwingen is recommended to develop targeted injury prevention guidelines.